(untitled) (Journal of EAHIL, 2021)
Where did 2020 go? For those of us in Australia who lived through the past year’s uncertainties and fears about COVID, weathering the restrictions of lockdowns and working-from-home (and for some, schooling from home); trying to make sense of the patchwork of state border controls, testing and quarantining requirements; and on top of all that, a faltering vaccination roll out, it was unthinkable that 2021 would bring more of the same. But more than half way through this year, it seems that we were overly optimistic that 2021 would see it all resolved. This is ‘take-two’, and we are getting used to a new COVID-normal.